QUALITY OF BROILER BREAST MEAT SUBJECTED TO DIFFERENT PROCESSING - GARCIA, Rodrigo Garófallo; NÄÄS, Irenilza de Alencar; CALDARA, Fabiana Ribeiro; DUARTE, Nilsa da Silva (Revista Brasileira de Engenharia de Biossistemas, 2010)
The objective was to evaluate the characteristics of breast meat of broiler chickens subjected to different solutions marination and aging time. Treatments were arranged in a 3x3 factorial arrangement with three different forms of marination (control-water, sodium chloride and monosodium glutamate) and three different times of maturation of the meat in the refrigerator (0, 24, and 48 hours) and were evaluated pH, weight loss by cooking (PPC), shear force (FC), water holding capacity (WHC), , loss of exudate (PE), sizing breast (DP) and sensory characteristics. The pH no significant change (p> 0.05) was presented at optimum acidification index. CPP and marinating was affected by the maturation period (p <0.05) having the lowest losses saline and the solution with higher losses as glutamate was increased aging time. HR showed that the fillets marinated in the saline solution in the three aging times were softer (p <0.001) than the control treatments and glutamate. The CRA was not influenced by the marination processos and maturation. The DP only the thickness were affected by treatments. Maturation in sensory analysis did not favor the attributes studied and the marination with salt or glutamate can be employed to improve tenderness, juiciness and palatability.